1979
DOI: 10.1107/s0567740879008372
|View full text |Cite
|
Sign up to set email alerts
|

Schiff-base complexes of calcium: crystal structure analysis of dinitrato[N,N'-propane-1,3-diylbis(salicylideneimine)]calcium(II) and the spectroscopic properties of some related complexes

Abstract: The title compound, [Ca(C 17H 18N202)(NO3)2], C17HlsCaN4Os, is orthorhombic with a = 37.166 (3), b = 10.181 (1), c = 5.111 (0) A, Z = 4, space group P2~2~2~. The structure was refined to R = 0.026 for 1511 counter reflections. The Schiff base is present in a hitherto unreported charge-separated form with the ligand bridging two Ca ions through negatively charged O atoms. The azomethine N atoms are not coordinated; they carry the protons which are transferred from the phenolic groups on complex formation and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The magnitudes of these hydrogen-bonding interactions are similar those reported for an analogous Schiff base complex [15]. Such proton transfer from oxygen to nitrogen atoms via hydrogen bond, and the formation of zwitterions in similar molecules to that discussed here, is quite commonly encountered [6,16,17] and facilitates coordination of the alkoxy or phenolic oxygens with the tin atoms.…”
Section: Crystal Structuresupporting
confidence: 71%
“…The magnitudes of these hydrogen-bonding interactions are similar those reported for an analogous Schiff base complex [15]. Such proton transfer from oxygen to nitrogen atoms via hydrogen bond, and the formation of zwitterions in similar molecules to that discussed here, is quite commonly encountered [6,16,17] and facilitates coordination of the alkoxy or phenolic oxygens with the tin atoms.…”
Section: Crystal Structuresupporting
confidence: 71%
“…However, Saraswat, Srivastava & Mehrotra (1979) from essentially identical infrared results reported that only the phenolic O atoms from the ligands are coordinated in the complexes, indicating that the intermediate zwitterion (lb) is predominant in the phenolimine (la)/ketoenamine (lc) equilibrium of Schiff bases. This is further substantiated by Bullock, Ladd, Povey & Tajmir-Riahi (1979) from the crystal structure and spectroscopic study of Schiff-base complexes of calcium nitrate.…”
mentioning
confidence: 77%
“…with the C=N+ frequencies, which were experimentally found (27,28) to be higher than the parent C=N groups. A strong absorption band at 1359 cm-' in the spectrum of the free base related to a pyrimidinic ring vibration (29) lost intensity and shifted to a higher frequency (1369 cm-') upon protonation.…”
Section: N7-protonntionmentioning
confidence: 89%